Involuntary and voluntary demotion: employeereactions and outcomes - Hennekam, Sophie; Ananthram, Subra (Taylor & Francis, 2020)
Demotion has received little attention from scholars and practitioners alike. The purpose of this study was to assess empirically the reaction to, and outcomes of, both involuntary and voluntary demotion. Drawing on 49 semi-structured in-depth interviews with 28 involuntarily demoted workers and 21 voluntarily demoted workers, we develop a conceptual model using organizational justice theory and person-job fit of the reaction to and outcomes of demotion. We show that involuntarily demoted individuals might react by expressing turnover intentions and lower motivation and commitment, indicating that the demotee’s reaction is related to perceptions of fairness. Voluntary demotion is related to a better work-life balance, greater satisfaction, less stress and burnout and is perceived to be a viable phased retirement option by older workers. In addition, the findings highlight the role of demotion-related stigma, status loss, identity threat, and age in the way employees react to the experience of demotion.